Bureaucratic discretion and alternative teacher certification: understanding program variation in Missouri. - Ethan B. Heinen; Jay Paredes Scribner (Arizona State University, 2007)
Alternative teacher certification literature has contributed significantly to our understanding of this approach to teacher preparation. However, this literature has more often than not treated alternative teacher certification programs (ATCPs) as a black box, thus ignoring program heterogeneity. The present study examines how and why five ATCPs in Missouri have evolved in different ways. To understand this variation and its potential significance for researchers and practitioners, we use political science literature on bureaucratic discretion to understand programs' varied responses within the same state policy context. Using a multiple case study design, we present two key findings. First, external factors such as the state's regulatory approach, programs' relationships with school districts, and programs' relationship with external partners shape program coordinators' perceptions of their discretionary authority. Second, within an environment of limited regulation, programs responded to these external factors in ways that shaped programs in dramatically different ways. These approaches ranged from formal partnerships with large urban school districts and philanthropic funders to alternative certification programs that were at least partially blended with existing undergraduate and post baccalaureate teacher preparation programs. In our discussion, we explore how state attempts to widen the discretionary space between the rules may have allowed external interests (e.g., school districts, and external funders) to backfill that space in ways that limit the potential for programs to provide high quality preparation experiences. This study explores these consequences and trade offs in order to inform policy makers and practitioners who are concerned with fostering innovative and creative ways to prepare high quality teachers.